The promise of planning : global aspirations and South African experience since 2008 - Harrison, Philip, 1964-; Todes, A. (New York : Routledge, 2024)
"The Promise of Planning explores the experience of planning internationally since the global financial crisis, focusing on South Africa. The book is a response to a decade-plus in which state-led planning has re-emerged as a putative means for achieving developmental goals (as indicated in global initiatives like the New Urban Agenda), and where planning in South Africa has consolidated in terms of its legal and policy basis. However, the return of planning is happening in an inauspicious context, with economic fragilities, technological shifts, political populism, institutional complexities, and more, threatening to upturn the 'new promise of planning'. The book provides a careful analytical account of planning in South Africa and how and why its promises have been difficult to achieve. Building on the authors' previous book, Planning and Transformation, the book sheds light on planning as an increasingly complex and diverse governmental practice within a perpetually changing world. It can be used as a resource for planners who must make good on the new promise of planning while navigating the risks and threats of the contemporary world, as well as students and faculty interested in international planning debates and the South African case"--
Keywords: Planning -- South Africa -- 21st century; Political planning -- South Africa -- 21st century; Policy sciences; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; SOCIAL SCIENCE / Sociology / Urban; HISTORY / Africa / South / South Africa